Towards a dynamic account of phraseological meaning: creative variation in headlines and conversational humour - Feyaerts, Kurt (International journal of English studies, 2006)
The present paper adopts a cognitive linguistic point of view from which it advocates a non-particularist perspective on the semantics of fixed expressions. It is shown, accordingly, that the semantic structure of fixed expressions can be analysed in terms of the various cognitive mechanisms of construal, which can be observed throughout all kinds of language use. In line with the cognitive linguistic tenet that meaning is essentially dynamic conceptualisation, generated in the constructivist act of the interacting subject, both analysability and motivation are discussed as two basic notions of phraseological semantics. The application of Langacker's 'Current Discourse Space' implies the consequent inclusion of discourse elements as an essential component of an integrated, usage-based account of (phraseological) semantics. Finally, the paper offers an empirical perspective in the description of the creative variation of fixed expressions in two different types of (mini)texts: newspaper headlines and conversational humour. KEYWORDS: Phraseological semantics, idioms, construal, analysability, motivation, creative variation, cognitive linguistics, discourse semantics, newspaper headlines, conversational humour